Effective strategies for formulating and articulating a well-defined research problem: context in the field of mathematics education - Rodríguez-Nieto, Camilo Andrés; Rodríguez-Vásquez, Flor Monserrat; Cantillo-Rudas, Benilda María; Font Moll, Vicenç; Sudirman, Sudirman (International Journal of Didactic Mathematics in Distance Education, 2025)
This research offers an answer to the question: How to pose and write a research problem in Mathematics Education? To do so, a qualitative descriptive methodology was implemented, developed in four stages: first, it presents a general overview of the Theories in Mathematics Education and some articles where relevant studies have been reported; in the second stage, the means by which research can be disseminated or published are presented; in the third, meanings and ways to pose a research problem are shown and, finally, in the fourth stage, some theoretical reflections on the problem statement are presented. The results show that the writing and statement of the problem does not necessarily follow a structure, that depends on the type of research and the way in which the author reports his ideas or in which theoretical framework he frames his work, for example, research questions from the Onto-semiotic Approach and the Extended Theory of Connections are presented. However, a special path is suggested that has worked very well to be implemented in future research. In conclusion, for research to be successful, the problem and the issue must be well constructed and supported by the literature, which guides and invites reflection on the choice of theory (if possible), the methodology and the presentation of the results that can be theoretical and practical.